Blood vessel diameter measurement on ultrasonic images - Udomhunsakul, Somkait; Hamamoto, Kazuhiko (My University, 2005)
Accurate measurement of blood vessel diameter on ultrasonic images is a potential part in diagnosis and physiological study. In this paper, a method of blood vessel diameter measurement has been presented. In our approach, we firstly used a histogram equalization technique to enhance the contrast of ultrasonic images. Secondly, a Guassian filter is used to remove the noisy pixels while preserving the important information. Next, we applied Haar wavelet filter to extract the blood vessel shape. Moreover, we used the nonmaxima suppression and thresholding techniques to get the blood vessel shape in the binary format. Finally, the users have to drag a mouse to measure the diameter of blood vessels. From the results, we found that our approach yields promising results compared with conventional methods and other mother wavelets. An ultrasonographer also confirmed the results. Therefore, our approach leads to an effective method for blood vessel diameter measurement.
Keywords: Blood vessel diameter measurement; Feature extraction; Medical image analysis; Ultrasonic images; Wavelet transforms